Nursing of a patient with acne treated by Chinese herbal medicine mask (中药面膜治疗痤疮1例的护理体会) - GENG Miaomiao (耿苗苗); SUN Mingli (孙明丽); TANG Ling (唐玲); XU Jingjin (徐京巾); GUO Xinyi (郭新一) (中西医结合护理)
This paper summarized the observation and nursing measures of a patient with acne treated by Chinese herbal medicine mask. Under the guidance of Traditional Chinese Medicine syndrome differentiation and pharmacological characteristics of the Chinese herbal mask, targeted nursing interventions were carried out to relieve the facial acne and negative emotion of the patient. (本文总结1例痤疮患者进行中药面膜治疗的观察及护理措施, 包括中药面膜的药理特性、使用方法、注意事项以及饮食、情志、生活等方面的护理措施, 通过中医辨证分型, 针对性予以干预, 有助改善患者面部痤疮, 缓解负性情绪。)